Effects of additional oral theophylline with inhaled therapy in patients with stable chronic obstructive pulmonary disease: A systematic review and meta-analysis - Qiang Yang; Pingxiu Tang,; Xunyan Zhang (PLoS ONE, 2025)
The rationale for additional treatment of oral theophylline with inhaled therapy in patients with stable chronic obstructive pulmonary disease (COPD) is unclear. The databases including The Cochrane Library､PubMed､Embase and Web of Science were searched to collect randomized controlled trials (RCTs) involving the inhaled therapy plus additional theophylline therapy for the treatment of patients with stable COPD up to December 31, 2023. The forced expiratory volume in 1 second (FEV1)､forced expiratory volume in 1s% predicted (FEV1% pred)､forced vital capacity (FVC)､FEV1/FVC%､peak expiratory flow rate(PEFR)､exacerbation rate of COPD､COPD related hospital admissions､total symptom score and drug-related adverse reactions were extracted from literatures and the meta-analysis was conducted using the RevMan 5.4 software. 10 RCTs involving 2771 patients were included. The meta-analysis results showed that additional theophylline improved FEV1 with MD 0.08 (95% CI: 0.06 to 0.09, p<0.00001)､FVC with MD 0.13 (95% CI: 0.10 to 0.15, p<0.00001), reduce the risk of exacerbation rate with OR 0.75 (95% CI: 0.60 to 0.94, p=0.01) and COPD related hospital admissions with MD -0.07 (95% CI: -0.13 to -0.01, p=0.01). However, there was no significant difference in FEV1% pred with MD 0.45 (95% CI: -1.41 to 2.30, p=0.64)､FEV1/FVC% with MD -0.24 (95% CI: -3.26 to 2.79, p=0.88) and total symptom score with MD -0.03 (95% CI: -0.14 to 0.09, p=0.65). Furthermore, additional theophylline therapy induced a high incidence of drug-related adverse reactions with OR 1.33 (95% CI: 1.12 to 1.58, p=0.001), especially in gastrointestinal adverse reactions. Oral theophylline could be a supplementary therapeutic option when inhaled therapy is insufficient regarding of improvement in pulmonary function and reducing in exacerbation risk. However, additional theophylline therapy could increase the risk of drug-related adverse reactions and should be concerned.